Preparation method of high-hydrophilic antibacterial polyethersulfone ultrafiltration membrane
By controlling the ratio of cast membrane liquid and controlling the phase separation speed, combining the synergistic effect of metal ions and hydrophilic substances in the cast membrane liquid, a high-hydrophilic antibacterial polyethersulfone ultrafiltration membrane was prepared, which solved the problems of existing membranes being easily contaminated, low water flux and poor interception, and achieved a balance between high hydrophilicity and excellent anti-pollution performance.
Patent Information
- Application Number
- CN202411600148.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-11-05
- Filing Date
- 2024-11-11
- Publication Date
- 2025-05-02
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
When the existing polyethersulfone ultrafiltration membranes weigh the hydrophilicity and antibacterial properties, they have problems such as easy pollution, low water flux, and poor interception, making it difficult to achieve high hydrophilicity and excellent anti-pollution properties at the same time.
By controlling the ratio of cast membrane liquid and controlling the phase separation speed, combining the synergistic effect of metal ions and hydrophilic substances in the cast membrane liquid, a highly hydrophilic and antibacterial polyethersulfone ultrafiltration membrane was prepared. The method includes blending the hydrophobic polymer polyether sulfone with a pore-generating agent and a polyphenol material to form a cast film liquid, and adding metal ions to the phase conversion liquid, so that the metal ions can penetrate into the film liquid through the curing process, forming a cover layer and modifying the pore structure.
The hydrophilicity and anti-fouling properties of the ultrafiltration membrane have been significantly improved, the water flux has been greatly improved, the BSA interception rate is higher than 99%, and the flux recovery rate can reach 90%. It is suitable for biomedical and clean energy fields.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of membrane preparation, and in particular relates to a method for preparing a polyethersulfone ultrafiltration membrane with high hydrophilicity and excellent antibacterial performance. Background Art
[0002] Membrane separation technology is a high-tech technology successfully developed in the 20th century, with the characteristics of novelty, high efficiency and precision. Ultrafiltration (UF) technology is widely used in water treatment, chemical industry, separation and purification, pharmaceutical industry and other fields due to its advantages of simple operation, wide application range, strong process applicability, strong selectivity, low energy consumption and no secondary pollution. In response to the needs of different industries, in-depth research has been conducted on ultrafiltration membranes. However, in terms of balancing hydrophilicity and antibacterial properties, there are still problems such as easy contamination, low water flux and poor retention. Therefore, achieving high hydrophilicity and excellent anti-pollution performance at the same time is still a major challenge.
[0003] Polyethersulfone (PES) is a polymer with good heat resistance, chemical corrosion resistance and excellent mechanical properties. It has good chemical stability and physical properties. However, the hydrophobicity of PES ultrafiltration membrane makes it easy to be contaminated. In the long-term filtration process, membrane pore blockage and biological contamination problems often lead to a decrease in permeation flux and filtration performance. Therefore, improving the hydrophilicity and antibacterial properties of PES ultrafiltration membrane is the key to solving membrane contamination.
[0004] By modifying the membrane to be hydrophilic, the hydrophobicity of the ultrafiltration membrane can be improved to enhance the antifouling ability of the ultrafiltration membrane. The method of preparing modified membranes by the NIPS method by mixing hydrophilic substances with membrane matrix materials in an organic solvent to form a casting solution is considered to be one of the convenient and effective methods to improve the hydrophilicity of the membrane and is a hot topic in the study of membrane hydrophilic modification. Depending on the casting solution formula and preparation process, the non-solvent-induced phase separation process can produce an asymmetric structure. The asymmetric ultrafiltration membrane has a selective top layer that only allows the desired species to pass through, and a bottom porous layer as a mechanical support, with an average pore size that varies along the membrane thickness. This structure is considered to be an ideal structure that takes into account both high flux and high retention rate. The ultrafiltration membranes currently developed cannot meet the needs of some market industries. Therefore, it is extremely urgent to propose a method for preparing a highly hydrophilic and anti-fouling ultrafiltration membrane that is simple to operate and low in cost. Summary of the invention
[0005] In view of the problem of poor compatibility of the comprehensive performance of the existing polyethersulfone ultrafiltration membrane, the present invention provides a method for preparing a highly hydrophilic antibacterial polyethersulfone ultrafiltration membrane. The method is characterized in that the ratio of the casting solution and the process control the phase separation speed, and the synergistic effect of the metal ions in the phase conversion solution and the hydrophilic substances in the casting solution greatly improve the hydrophilic and antifouling properties of the PES membrane, the water flux is also greatly improved, and a good retention rate for BSA is retained.
[0006] In order to solve the above problems, the present invention provides a method for preparing a highly hydrophilic antibacterial polyethersulfone ultrafiltration membrane, and the technical solution adopted is: First, a hydrophobic polymer polyethersulfone is dissolved in a solvent, and then a porogen and a polyphenol material are added, and the mixture is heated and stirred for 10-14 hours to obtain a casting solution, and the casting solution is allowed to stand for degassing and standby; wherein the casting solution is prepared by the following components in percentage by mass: 15-20% polyethersulfone, 30-45% porogen, 2.5-12.5% polyphenol material, and the balance is solvent; Secondly, metal ions are added to the aqueous solution to prepare a phase conversion solution, and the concentration of the metal ions in the phase conversion solution is adjusted to 0.25-1 mol / L for standby use; the added metal ions are one or more of silver nitrate, cupric chloride, zinc chloride, ferric chloride, or cupric chloride.
[0007] Finally, in an air atmosphere with a relative humidity of 40-70%, a scraper is used to spread the prepared casting liquid on the surface of the non-woven fabric to form a thin layer with a thickness of 150-250 μm, and then immersed in the prepared metal ion phase conversion liquid for curing for 10-30 minutes, so that the curing liquid invades the interior of the membrane liquid and gradually diffuses inward; after the film is cured, it is taken out and rinsed with pure water to obtain a highly hydrophilic and antibacterial polyethersulfone ultrafiltration membrane.
[0008] The organic solvent is one of N,N-dimethylacetamide, N,N-dimethylformamide, dimethyl sulfoxide and N-methylpyrrolidone.
[0009] Among them, the porogen is polyethylene glycol (MW=400-8000), polyvinyl pyrrolidone, or one of polyvinyl acetate.
[0010] Among them, the polyphenol material is one of dopamine, tannic acid, tea polyphenols, catechol and pyrogallol.
[0011] The stirring and dissolving time is 10-14 h.
[0012] Wherein, the metal ions in the metal ion phase conversion solution are one or more of silver nitrate, copper chloride, zinc chloride, ferric chloride, or copper chloride.
[0013] The curing time of immersing in the coagulation bath is 10-30 min.
[0014] The present invention also provides a method for preparing a highly hydrophilic antibacterial polyethersulfone ultrafiltration membrane. The composite membrane is highly hydrophilic and has a flux recovery rate of up to 90% and a BSA retention rate of >99%.
[0015] Compared with the prior art, the present invention has significant advantages: 1. The polyethersulfone ultrafiltration membrane prepared by the integrated membrane forming of the present invention has a surface layer covered with a metal ion-catechol chelate, and the internal pore structure of the membrane is also modified. Compared with the original membrane, the membrane pore size is overall reduced and evenly distributed, and has greatly improved performance compared with the ultrafiltration membrane of the prior art. The reason for the improvement is that the polymer network with catechol serves as a polymer scaffold, and the metal ions are nucleated at the polymer cross-linking sites through the metal ligand coordination between the metal ions and catechol, achieving in-situ mineralization and being well dispersed in the metal-coordinated polymer network, which plays a key role in improving the hydrophilicity and mechanical properties of the polymer membrane.
[0016] 2. Different from the ultrafiltration membrane prepared by conventional methods, the highly hydrophilic and antibacterial polyethersulfone ultrafiltration membrane prepared by the present invention has a thin sponge-like pore layer and a uniform finger-like pore structure, which effectively improves the permeation flux and retention rate of the ultrafiltration membrane. The BSA retention rate is >99%, and it has a high flux recovery rate of up to 90%. It has broad application prospects in the fields of biomedicine and clean energy. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 is an image of the casting solution in Example 1; Figure 2 This is a comparison diagram of the ultrafiltration membrane entity obtained in Example 2; Figure 3 This is a cross-sectional SEM image of the ultrafiltration membrane obtained in Example 3; Figure 4 This is a surface SEM image of the ultrafiltration membrane obtained in Example 4; Figure 5 This is the water contact angle diagram of the ultrafiltration membrane prepared in Example 5. DETAILED DESCRIPTION
[0018] The present invention is further described below in conjunction with specific embodiments. Example
[0019] Step 1): The casting solution is prepared by the following components in percentage by mass: 15% polyethersulfone, 30% polyethylene glycol (MW = 400), 2.5% dopamine, and the balance is N, N-dimethylacetamide; polyethersulfone is a hydrophobic polymer, which is dissolved in N, N-dimethylacetamide and then polyethylene glycol (MW = 400) and dopamine are added, heated and stirred for 10 hours to obtain a casting solution, which is then allowed to stand for degassing and set aside; the prepared casting solution is as follows Figure 1 As shown, it is yellow and transparent.
[0020] Step 2): Add silver nitrate to the aqueous solution to adjust the concentration of metal ions in the phase conversion solution to 0.25 mol / L for standby use; Step 3): In an air atmosphere with a relative humidity of 40%, the casting solution prepared in step (1) is spread on the surface of the polypropylene non-woven fabric using a scraper to form a thin layer with a thickness of 150 μm, and then immersed in the metal ion phase conversion solution prepared in step (2) for curing for 10 minutes, so that the curing solution invades the inside of the membrane solution and gradually diffuses inward; after the film is cured, it is taken out and rinsed with pure water to obtain a highly hydrophilic antibacterial polyethersulfone ultrafiltration membrane. The original membrane flux recovery rate can only reach 60%, the composite membrane is highly hydrophilic and the flux recovery rate can reach 90%, and the BSA retention rate is >99.1%. Example
[0021] Step 1): The casting solution is prepared by the following components in percentage by mass: 20% polyethersulfone, 45% polyethylene glycol (MW=8000), 12.5% tannic acid, and the balance is N,N-dimethylformamide; polyethersulfone is a hydrophobic polymer, which is dissolved in N,N-dimethylformamide and then polyethylene glycol (MW=8000) and tannic acid are added, heated and stirred for 14 h to obtain the casting solution, which is then allowed to stand for degassing and standby; Step 2): Add ferric chloride to the aqueous solution to adjust the concentration of metal ions in the phase conversion solution to 0.75 mol / L for standby use; Step 3): In an air atmosphere with a relative humidity of 70%, use a scraper to spread the casting solution prepared in step (1) on the surface of the polyester non-woven fabric to form a thin layer with a thickness of 250 μm, and then immerse it in the metal ion phase conversion solution prepared in step (2) for curing for 30 minutes, so that the curing solution invades the inside of the membrane solution and gradually diffuses inward; after the film is cured, take it out and rinse it with pure water to obtain a highly hydrophilic antibacterial polyethersulfone ultrafiltration membrane. Figure 2 As shown, the entire membrane has been covered with metal ions and is evenly distributed. The flux recovery rate of the original membrane can only reach 60%, while the composite membrane is highly hydrophilic and has a flux recovery rate of 92%, and a BSA retention rate of >99.6%, which is significantly improved compared to the original membrane. Example
[0022] Step 1): The casting solution is prepared by the following components in percentage by mass: 17% polyethersulfone, 40% polyvinylpyrrolidone, 10% tea polyphenols, and the balance is dimethyl sulfoxide; polyethersulfone is a hydrophobic polymer, which is dissolved in dimethyl sulfoxide and then polyvinylpyrrolidone and tea polyphenols are added, heated and stirred for 12 hours to obtain the casting solution, which is then allowed to stand for degassing and set aside; Step 2): Add zinc chloride to the aqueous solution to adjust the concentration of metal ions in the phase conversion solution to 0.5 mol / L for standby use; Step 3): In an air atmosphere with a relative humidity of 50%, use a scraper to spread the casting solution prepared in step (1) on the surface of the polyamide non-woven fabric to form a thin layer with a thickness of 200 μm, and then immerse it in the metal ion phase conversion solution prepared in step (2) for curing for 20 minutes, so that the curing solution invades the interior of the membrane liquid and gradually diffuses inward; after the film is cured, take it out and rinse it with pure water to obtain a highly hydrophilic antibacterial polyethersulfone ultrafiltration membrane. The original membrane flux recovery rate can only reach 60%, the composite membrane is highly hydrophilic and the flux recovery rate can reach 93%, and the BSA retention rate is >99.5%. The cross-sectional SEM image of the membrane is shown in the figure Figure 3 As shown, the membrane has typical finger-like pores and sponge-like pores of ultrafiltration membranes, smaller finger-like pores than the original membrane and a uniform distribution of pore sizes. Example
[0023] Step 1): The casting solution is prepared by the following components in percentage by mass: 16% polyethersulfone, 37% polyvinyl acetate, 7.5% catechol, and the balance is N-methylpyrrolidone; polyethersulfone is a hydrophobic polymer, which is dissolved in N-methylpyrrolidone and then polyvinyl acetate and catechol are added, heated and stirred for 11 h to obtain the casting solution, which is then allowed to stand for degassing and set aside; Step 2): Add ferric chloride and cupric chloride to the aqueous solution to adjust the concentration of metal ions in the phase conversion solution to 0.75 mol / L for standby use; Step 3): In an air atmosphere with a relative humidity of 60%, use a scraper to spread the casting solution prepared in step (1) on the surface of the viscose fiber non-woven fabric to form a thin layer with a thickness of 250 μm, and then immerse it in the metal ion phase conversion solution prepared in step (2) for curing for 15 minutes, so that the curing solution invades the inside of the membrane solution and gradually diffuses inward; after the membrane is cured, take it out and rinse it with pure water to obtain a highly hydrophilic antibacterial polyethersulfone ultrafiltration membrane. The surface SEM image of the membrane is shown in the figure Figure 4 As shown in Figure 2, it can be clearly seen that the membrane surface is covered with metal ions. Figure 2 The changes before and after the middle membrane are consistent. The flux recovery rate of the original membrane can only reach 60%, the composite membrane is highly hydrophilic and the flux recovery rate can reach 91%, and the BSA retention rate is >99.4%. Example
[0024] Step 1): The casting solution is prepared by the following components in mass percentage: 18% polyethersulfone, 40% polyethylene glycol (MW=6000), 5% pyrogallol, and the balance is N,N-dimethylacetamide; polyethersulfone is a hydrophobic polymer, which is dissolved in N,N-dimethylacetamide and then polyethylene glycol (MW=6000) and pyrogallol are added, heated and stirred for 12 h to obtain the casting solution, which is then allowed to stand for degassing and set aside; Step 2): Add copper chloride to the aqueous solution to adjust the concentration of metal ions in the phase conversion solution to 0.25 mol / L for standby use; Step 3): In an air atmosphere with a relative humidity of 50%, use a scraper to spread the casting solution prepared in step (1) on the surface of the polyamide non-woven fabric to form a thin layer with a thickness of 200 μm, and then immerse it in the metal ion phase conversion solution prepared in step (2) for curing for 25 minutes, so that the curing solution invades the inside of the membrane solution and gradually diffuses inward; after the film is cured, take it out and rinse it with pure water to obtain a highly hydrophilic antibacterial polyethersulfone ultrafiltration membrane. The water contact angle of the ultrafiltration membrane before and after modification is as follows Figure 5 As shown, compared with the original membrane, the water contact angle is greatly reduced and the hydrophilicity is greatly improved. The flux recovery rate of the original membrane can only reach 60%, while the composite membrane is highly hydrophilic and the flux recovery rate can reach 90%, and the BSA retention rate is >99.8%.
Claims
1. A method for preparing a highly hydrophilic antibacterial polyethersulfone ultrafiltration membrane. Characterized in that: The following steps are involved: (1) The casting solution is prepared by the following components in percentage by mass: 15-20% polyethersulfone, 30-45% porogen, 2.5-12.5% polyphenol material, and the balance is solvent; polyethersulfone is a hydrophobic polymer, which is dissolved in a solvent, and then the porogen and polyphenol material are added, heated and stirred for 10-14 h to obtain a casting solution, which is then allowed to stand for degassing and set aside; (2) adding metal ions to the aqueous solution to adjust the concentration of the metal ions in the phase conversion solution to 0.25-1 mol / L for standby use; the added metal ions are one or more of silver nitrate, copper chloride, zinc chloride, ferric chloride, or copper chloride; (3) In an air atmosphere with a relative humidity of 40-70%, use a scraper to spread the casting solution prepared in step (1) on the surface of the non-woven fabric to form a thin layer with a thickness of 150-250 μm, and then immerse it in the metal ion phase conversion solution prepared in step (2) for curing for 10-30 min, so that the curing solution invades the interior of the membrane liquid and gradually diffuses inward; after the film is cured, take it out and rinse it with pure water to obtain a highly hydrophilic antibacterial polyethersulfone ultrafiltration membrane.
2. The method for preparing a highly hydrophilic antibacterial polyethersulfone ultrafiltration membrane according to claim 1, wherein the organic solvent is one of N,N-dimethylacetamide, N,N-dimethylformamide, dimethyl sulfoxide, and N-methylpyrrolidone.
3. The method for preparing a highly hydrophilic antibacterial polyethersulfone ultrafiltration membrane according to claim 1, wherein the porogen is one of polyethylene glycol (MW = 400-8000), polyvinyl pyrrolidone, and polyvinyl acetate.
4. The method for preparing a highly hydrophilic antibacterial polyethersulfone ultrafiltration membrane according to claim 1, wherein the polyphenol material is one of dopamine, tannic acid, tea polyphenols, catechol and pyrogallol.
5. The method for preparing a highly hydrophilic antibacterial polyethersulfone ultrafiltration membrane according to claim 1, characterized in that: The non-woven fabric in step (3) is one of polypropylene non-woven fabric, polyester non-woven fabric, polyamide non-woven fabric and viscose fiber non-woven fabric.
6. A method for preparing a highly hydrophilic antibacterial polyethersulfone ultrafiltration membrane according to any one of claims 1 to 5, wherein the prepared highly hydrophilic antibacterial polyethersulfone ultrafiltration membrane is characterized in that: The composite membrane is highly hydrophilic and has a flux recovery rate of up to 90% and a BSA retention rate of >99%.
Citation Information
Patent Citations
Preparation method of small-aperture anti-pollution ultrafiltration membrane for protein interception
CN116328554A
Cited By
Ultrafiltration membrane based on metalloporphyrin modification
CN120618280A